Eksistensi Modal Sosial Petani Sawit Di Desa Sidomulyo Kecamatan Wanaraya Kabupaten Barito Kuala - Nur, Rahmat; Hidayat, Yusuf; Azis, Fatima (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This research is focused on the study of the social capital of oil palm farmers in Sidomulyo Village, Wanaraya District, Barito Kuala Regency, South Kalimantan Province. This study aims to: first, identify the social capital owned by oil palm independent smallholders. Second, describe the maintenance of their social capital. This study uses qualitative research methods to gain a deep understanding of the social capital of independent smallholders that supports their success in the management of oil palm plantations. This research was conducted in Sidomulyo village, Wanaraya district, Barito Kuala Regency, South Kalimantan Province. Informants as sources of information were selected using purposive sampling technique. Data mining was carried out by observation, in-depth interviews (in-depth interviews) with selected informants and diaries are one of the important data sources in the research used in this study.. This study found: (1) Forms of social networks built by farmers and middlemen to sell oil palm to palm oil processing companies. (2) Their membership in farmer groups (3) The work ethic of the farmers as a transmigrant.